2020
DOI: 10.1101/2020.01.25.917617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time varying connectivity across the brain changes as a function of nicotine abstinence state

Abstract: Background:The Nicotine Withdrawal Syndrome (NWS) includes affective and cognitive disruptions whose incidence and severity vary across time during acute abstinence. However, most network-level neuroimaging employs static measures of resting state functional connectivity (rsFC), assuming time-invariance, and unable to capture dynamic brain-behavior relationships. Recent advances in rsFC signal processing allow characterization of "time varying connectivity" (TVC), which characterizes network communication betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, existing research has unveiled that smokers and non-smokers exhibit distinctive resting-state indices related to dynamic changes in localized neural activity, such as dynamic regional homogeneity (dReHo) and dynamic amplitude of low-frequency fluctuations (dALFF) (18). Previous studies employing dynamic functional connectivity (dFC) methods have found that smokers experience reduced temporal flexibility and spatiotemporal diversity in brain networks during acute withdrawal (19). However, there is a lack of systematic research on dFC of the insula subregions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing research has unveiled that smokers and non-smokers exhibit distinctive resting-state indices related to dynamic changes in localized neural activity, such as dynamic regional homogeneity (dReHo) and dynamic amplitude of low-frequency fluctuations (dALFF) (18). Previous studies employing dynamic functional connectivity (dFC) methods have found that smokers experience reduced temporal flexibility and spatiotemporal diversity in brain networks during acute withdrawal (19). However, there is a lack of systematic research on dFC of the insula subregions.…”
Section: Introductionmentioning
confidence: 99%